2001
DOI: 10.1023/a:1012225108281
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The processing of emotional expressions is fundamental for normal socialisation and interaction. Reduced responsiveness to the expressions of sadness and fear has been implicated in the development of psychopathy (R. J. R. Blair, 1995). The current study investigates the sensitivity of children with psychopathic tendencies to facial expressions. Children with psychopathic tendencies and a comparison group, as defined by the Psychopathy Screening Device (PSD; P. J. Frick & R. D. Hare, in press), were presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
201
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(218 citation statements)
references
References 24 publications
13
201
2
2
Order By: Relevance
“…A signifi cant proportion of these studies have presented stimuli for three seconds (Blair & Cipolotti, 2000;Blair & Coles, 2000;Blair, Colledge, Murray, & Mitchell, 2001;Blair et al, 2004;Mitchell, Avny, & Blair, 2006). Other studies utilized periods longer than three seconds (McCown, Johnson, & Austin, 1986;Pham & Philippot, 2010;Walz & Benson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A signifi cant proportion of these studies have presented stimuli for three seconds (Blair & Cipolotti, 2000;Blair & Coles, 2000;Blair, Colledge, Murray, & Mitchell, 2001;Blair et al, 2004;Mitchell, Avny, & Blair, 2006). Other studies utilized periods longer than three seconds (McCown, Johnson, & Austin, 1986;Pham & Philippot, 2010;Walz & Benson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Blair et al [22] put forward a specific deficit for identifying emotions that reflect distress, such as fear and sadness. Typically, developing individuals interpret fear and sadness in others as aversive and when an aggressive act is carried out and an expression of fear or sadness observed, in classical conditioning this act is perceived to be aversive and is inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Psychopathic subjects often present a good, though superficial, ability to understand social signals [17]. Despite this, it has been shown that these subjects often have specific impairments in recognizing sad and fearful facial expressions [18,19], as well as more global impairment in identifying facial expressions [6]. Regardless of the fact that both groups (ASD and PSY) demonstrate impairment in recognizing emotional facial expressions, the different clinical symptoms shown in these two groups could possible correspond to recruitment of different brain networks when processing various facial expressions.…”
Section: Introductionmentioning
confidence: 99%